The role of circadian rhythms in the hypertension of diabetes mellitus and the metabolic syndrome - Lemmer, Björn; Oster, Henrik (Current hypertension reports, 2018)
Cellular circadian clocks regulate physiological functions during day and night. It has been convincingly demonstrated that hypertension in patients suffering from diabetes mellitus or metabolic syndrome is characterized in most cases by a disturbed 24-h profile resulting in a nondipper pattern. We consider possible correlation between biological clocks and symptoms of the metabolic syndrome.